A Scoping Review of Home-Based Vestibular Rehabilitation for Benign Paroxysmal Positional Vertigo Patients - Mustafa, Hizami; Omar, Norazreen; Alghwiri, Alia A; Manaf, Haidzir (Malaysian Journal of Medical Sciences, 2025)
Benign paroxysmal positional vertigo (BPPV) is a common vestibular disorder among older adults, characterised by dizziness and imbalance caused by the displacement of otoconia into the semicircular canals. Although canalith repositioning manoeuvres are considered the standard treatment, their high recurrence rate and the need for frequent clinic visits highlight the demand for supplementary therapeutic approaches. This review examines the effectiveness of home-based vestibular rehabilitation and the associated challenges in managing patients with BPPV. A comprehensive search of databases including PubMed, Scopus, Science Direct, Web of Science, PEDro, Mendeley, and Google Scholar identified 251 records using keywords such as “BPPV” and “home-based exercise rehabilitation.” Following the screening of 228 records and full-text review of 172 articles, 17 studies met the inclusion criteria. The total sample included 541 patients with BPPV, with intervention group sizes ranging from 10 to 154 and control group sizes from 10 to 151. Intervention durations varied between 1 and 24 weeks. The findings indicate that home-based rehabilitation can reduce dizziness, improve balance and gait, lower fall risk, and enhance quality of life. Digital tools such as telephone consultations and online platforms were frequently used to support adherence and monitor exercise performance. However, the effectiveness varied across studies, with some reporting substantial benefits and others showing limited improvements. This review highlights the potential of digital technologies in enhancing home-based vestibular rehabilitation, while also emphasising the need for further research to optimise protocols and assess long-term outcomes.